Evaluation of synthetic insecticides on Metamasius spinolae (Coleoptera: Curculionidae) adults from Tlalnepantla, Morelos - Cerón-González, Claudia; Rodríguez-Leyva, Esteban; Lomeli-Flores, J. Refugio; Hernández-Olmos, Claudia E.; Peña- Martínez, Rebeca; Mora-Aguilera, Gustavo (Revista Mexicana de Ciencias Agrícolas, 2018)
The cactus weevil, Metamasius spinolae (Gyllenhal), is one of the most important pests in prickly pear (Opuntia ficus-indica (L.) Miller) in Mexico and especially in Tlalnepantla, Morelos, the second most important region in the production of this crop, with about 2 500 ha. Both adults and larvae cause damage to this crop; larvae make galleries in mature pads and adults damage young pads of the cactus. Although there are no authorized pesticides for its control in Mexico, this fact does not stop farmers from using synthetic insecticides without knowing their effectiveness. For this reason, this study evaluated the effectiveness of eight pesticides in two chemical groups, organophosphates and pyrethroids, on adults of this insect. The laboratory and field tests conducted in 2007 showed that malathion caused a mortality similar to other more toxic products in the same group (Methyl Parathion and Methidathion). On the other hand, only a pyrethroid insecticide (Permethrin) provided a mortality rate close to 86%, in comparison to the remaining three (Cypermethrin, Deltamethrin and Fenvalerate) which caused a mortality of under 20% mortality. There was a differential response of the sex of the insect to insecticides, in which females were less susceptible than males to some products, such as Diazinon, Permethrin and Cypermethrin. This is the first formal report of the evaluation of synthetic insecticides in this insect and we discuss some issues related to management.
Keywords: Opuntia; chemical control; pests; weevils